2015
DOI: 10.1007/s11356-015-4296-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxoplasma gondii levels in zebra mussel (Dreissena polymorpha) by real-time PCR: an organotropism study

Abstract: Water quality is a public health concern that calls for relevant biomonitoring programs. Molecular tools such as polymerase chain reaction (PCR) are progressively becoming more sensitive and more specific than conventional techniques to detect pathogens in environmental samples such as water and organisms. The zebra mussel (Dreissena polymorpha) has already been demonstrated to accumulate and concentrate various human waterborne pathogens. In this study, first, a spiking experiment to evaluate detection levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This detection level seems low, but compared to laboratory studies, it corresponds to the level found during the first 2 weeks of a 21‐day in vivo exposure to 1000 oocysts per mussel and per day (Palos Ladeiro et al . ). The sensitivity of the PCR method may have been affected by PCR inhibitors because shellfish homogenates are often laden with soil, sediment, organic matter, as well as chemical and biological pollutants (Castro‐Hermida et al .…”
Section: Discussionmentioning
confidence: 97%
“…This detection level seems low, but compared to laboratory studies, it corresponds to the level found during the first 2 weeks of a 21‐day in vivo exposure to 1000 oocysts per mussel and per day (Palos Ladeiro et al . ). The sensitivity of the PCR method may have been affected by PCR inhibitors because shellfish homogenates are often laden with soil, sediment, organic matter, as well as chemical and biological pollutants (Castro‐Hermida et al .…”
Section: Discussionmentioning
confidence: 97%
“…This study also shows that mussels accumulate protozoan proportionally to water contamination. Moreover, T. gondii was still present in the mussel tissues for up to 14 days postinoculation, reflecting the integrative character of D. polymorpha [27]. A field study was also carried out in order to test protozoa detection under environmental conditions.…”
Section: Protozoa Pathogensmentioning
confidence: 99%
“…The reasons for the scanty application of molecular technique include lack of funds, poor electricity supply for specimen preservation and lack/ shortage of trained personnel. The use of this approach cannot be overemphasised giving the advantages it has over other diagnostic techniques (Ajmal et al 2013, Wang et al 2014, Palos Ladeiro et al 2015, Shapiro et al 2015.…”
Section: Genetic Diversity Of Strains Of T Gondii In Nigeriamentioning
confidence: 99%